The effect of crop rotation and tillage practice on soil moisture, nitrogen mineralisation, growth, development, yield and quality of wheat produced in the Swartland area of South Africa - Wiese, Jacobus Daniel (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScAgric)--Stellenbosch University, 2013.